2022
DOI: 10.3390/ijerph19063413
|View full text |Cite
|
Sign up to set email alerts
|

Health, Psychological and Demographic Predictors of Depression in People with Fibromyalgia and Osteoarthritis

Abstract: Depression is common in people with fibromyalgia (FM) and osteoarthritis (OA) and has been linked to adverse health outcomes in these conditions. The purpose of this study was to examine differences in predictors of depression among individuals with FM and OA using a range of health, demographic, and psychological variables. Of the total 963 participants, 600 were diagnosed with FM, and 363 with OA. The Quality of Well-Being Scale (QWB) was used to assess health status. The Fibromyalgia Impact Questionnaire (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Barowsky et al [11] show that osteoarthritis and major depression appear to share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus that should be explored further. As well, this research points to the strong impact of depression on the health status and general condition of the adult with osteoarthritis, that occurs more often in the case where the adult feels helpless and unconfident [12], and may induce a deleterious impact on management in general, as well as on surgery outcomes where this is needed [3,13].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Barowsky et al [11] show that osteoarthritis and major depression appear to share common genetic risk mechanisms, one of which centers on the neural response to the sensation of mechanical stimulus that should be explored further. As well, this research points to the strong impact of depression on the health status and general condition of the adult with osteoarthritis, that occurs more often in the case where the adult feels helpless and unconfident [12], and may induce a deleterious impact on management in general, as well as on surgery outcomes where this is needed [3,13].…”
Section: Resultsmentioning
confidence: 76%
“…At the same time, those experiencing psychological distress may be less motivated towards self-care, as well as less optimistic about engaging in treatments deemed crucial for minimizing their disability such as exercise [53,54], and may yet have a lower life quality, higher pain and body mass scores plus more stiffness than desirable in spite of receiving a surgical joint replacement to counter this [13,54]. those with no depression [56].…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, the LooH with a spiritual component improved the patients' functional status and reduced anxiety. Knee OA is associated with both physical and psychological problems (Van Dyne et al, 2022). Reiki opens and balances the energy flow path and centers in individuals and heals physical, psychological, and emotional problems (Midilli & Eser, 2015), thereby providing relaxation and a sense of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for example, in rheumatoid arthritis it has been reported that the dominant predictors of self-reported depression are pain and fatigue and it is considered that these may be the main cause of the depression [41,42]. Depression in fibromyalgia is also associated with severity of pain and degree of impairment but, in addition, depression in fibromyalgia is closely associated with psychological variables such as neuroticism, learned helplessness, low self-efficacy and with psychosocial problems [43][44][45][46]. These psychological variables are associated also with depression in the absence of physical illness [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%